Finite Element Analysis of Maximum Electric Field for Air Breakdown under Various Electrode Configurations - Nur Farhani Ambo; Hidayat Zainuddin; Muhammad Saufi Kamarudin; Jamaludin Mohd Wari; Ayuamira Zahari (Institute of Advanced Engineering and Science, 2018)
This paper describes the electric field behavior of air breakdown under various electrode configurations and gap length. By using COMSOL Multiphysics, a Finite Element Method (FEM) software, the values of maximum electric field can be determined based on the air breakdown voltage data obtained from the experiment under AC stress. The results show that R0.5-plane configuration provides a very high electric field upon breakdown, compared to R6-plane, R48-plane and plane-plane configurations. In addition, the comparison between the analytical and simulation results of maximum electrical field gives almost identical results for each electrode configuration except for R6-plane.